Canning of Squid - VARMA, P R.G; JOSEPH, JOSE (Fishery Technology, 2017)
A simple method for canning squid ( Loligo sp.) is discussed. Hot blanching the dressed meat in 7% brine containing 0.2% citric acid for 5 min, packing and subsequent filln?-g with 2% brine containing 0.2% citric acid and processing at 1.0 kgjcm2 steam for 20 mm gave an excellent canned product with good shelf-life